Willingness and Influencing Factors to Receive COVID-19 Vaccination Among Chinese Medical Students - Liu, Huan; Zhou, Zhiqing; Tao, Xiubin; Huang, Long; Zhu, Ergang; Yu, Liang; Du, Shaoling; Zhang, Ming (Frontiers in Public Health, 2022)
Objectives The study aimed to examine medical students’ willingness to receive COVID-19 vaccination in China and and explore the reasons for their decision. Methods A cross-sectional survey was conducted from 11 March and 12 March 2021, by administering an online questionnaire to the Chinese medical students. Data entry and analysis were conducted using IBM SPSS ver. 26.0. Results Of 3047 students who completed the survey, 37.9%（1154）of participants indicated that they would be vaccinated against COVID-19, while 62.1% (1893) declared that they would not. Attitudes to the COVID-19 vaccine (p= 0.000), Levels of eHealth Literacy(p=0.000), The impact of COVID19 on you(p=0.000), Concerns about the COVID-19 vaccine(p=0.000) and Sex (p= 0.000) strong associations of willingness to receive the COVID-19 vaccine. Conclusion The willingness to receive COVID-19 vaccination was sub-optimal among medical students in China. Educational interventions to improve medical students' perceptions and acceptance toward the COVID-19 vaccine are needed.